2016
DOI: 10.5897/ajb2015.14883
|View full text |Cite
|
Sign up to set email alerts
|

A commercial micropropagation protocol for virupakshi (AAB) banana via apical meristem

Abstract: In vitro micropropagation of banana (Musa spp.) cv.virupakshi (Hillbanana) was studied. Suckers were collected from the germ plasm block of Jain R&D (originally established from the suckers from Palani Hills, Tamil Nadu) during summer. The sucker surface sterilized with 1% NaOCl for 30 min gave 100% survival without any contamination. Apical meristems that were isolated and cultured on MS based media supplemented with benzylaminopurine (BAP) 10.0 mg/l and IAA1.0 mg/l gave higher number of shoots (134.3 shoots/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…The optimum and effective treatment of cytokinin for fruitful shoot multiplication of the cultivar Gopi was recorded in MS medium supplemented with BAP 8mg l -1 during 42 days old culture (Table 1). However, previous reports on banana micropropagation demonstrated the use of MS medium fortified with BAP and IAA proving as the effectual combination and providing with the desired outcomes concerning rapid shoot initiation [15][16][17]. Several reports on tissue culture of banana have also been reported by different workers using cytokinin as a principal growth regulator for induction and multiplication of shoot bud formation [5,[18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The optimum and effective treatment of cytokinin for fruitful shoot multiplication of the cultivar Gopi was recorded in MS medium supplemented with BAP 8mg l -1 during 42 days old culture (Table 1). However, previous reports on banana micropropagation demonstrated the use of MS medium fortified with BAP and IAA proving as the effectual combination and providing with the desired outcomes concerning rapid shoot initiation [15][16][17]. Several reports on tissue culture of banana have also been reported by different workers using cytokinin as a principal growth regulator for induction and multiplication of shoot bud formation [5,[18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Kishor et al, (2017) used cocopeat and vermiculite in 1:1 ratio for optimum growth and development. Karule et al, (2016) reported acclimatization of plantlets in polyhouse, followed by shadenet house under 50% sunlight and the plants showed luxurious growth in field (Table 5) (Fig. 1-7).…”
Section: Acclimatization and Hardening Of Plantletsmentioning
confidence: 90%
“…Poovan has been well expressed as all the explants proliferated in most of the media tested. Shoot tip explant has been identified as the preferred material for micropropagation for a wide range of banana cultivars such as 'Mehersagar' (Rahman et al,2006), 'Basrai' (Muhammad et al, 2007), 'Virupakshi' (Karule et al, 2016). However, immature inflorescence tip has also been employed for micropropagation in different cultivars (Resmi and Nair, 2007;Mahadevet al, 2011).…”
Section: Discussion:-mentioning
confidence: 99%